Chlorinated Enyne Fatty Acid Amides from a Marine Cyanobacterium: Discovery of Taveuniamides L-M and Pharmacological Characterization of Taveuniamide F as a GPCR Antagonist with CNR1 Selectivity - Lobna A. Elsadek; Emma K. Ellis; Gustavo Seabra; Valerie J. Paul; Hendrik Luesch (Marine Drugs, 2023)
NMR and MS/MS-based metabolomics of a cyanobacterial extract from Piti Bomb Holes, Guam, indicated the presence of unique enyne-containing halogenated fatty acid amides. We isolated three new compounds of this class, taveuniamides L-N (1–3), along with the previously reported taveuniamide F (4), which was the most abundant analog. The planar structures of the new compounds were established using 1D and 2D NMR as well as mass spectrometry. We established the configuration of this chemical class to be R at C-8 via Mosher’s analysis of 4 after reduction of the carboxamide group. Our biological investigations with 4 revealed that the compound binds to the cannabinoid receptor CNR1, acting as an antagonist/inverse agonist in the canonical G-protein signaling pathways. In selectivity profiling against 168 GPCR targets using the β-arrestin functional assay, we found that 4 antagonizes GPR119, NPSR1b, CCR9, CHRM4, GPR120, HTR2A, and GPR103, in addition to CNR1. Interestingly, 4 showed a 6.8-fold selectivity for CNR1 over CNR2. The binding mode of 4 to CNR1 was investigated using docking and molecular dynamics simulations with both natural and unnatural stereoisomers, revealing important CNR1 residues for the interaction and also providing a possible reasoning for the observed CNR1/CNR2 selectivity.